Evaluation of the Learning Quality of the Agricultural Industrial Technology Study Program Using Customer Satisfaction Index (CSI) And Importance-Performance Analysis (IPA) - Andi Muhammad Akram Mukhlis; Syahrul Syahrul; Baso Intang Sappaile (Sakura Digital Nusantara, 2026)
Purpose: This study analyzes the learning process quality in the Agricultural Industrial Technology Program at Universitas Negeri Makassar by evaluating satisfaction, analyzing gaps, and mapping priority attributes to provide data-driven management recommendations. Methods: This descriptive quantitative survey involved 121 active students, split into pilot and main groups. Content validity was verified using Aiken’s V with 5 experts. Construct validity was tested via Confirmatory Factor Analysis (CFA) in JASP, and reliability via Cronbach's Alpha. Data analysis integrated the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA). Findings: Aiken's V confirmed content validity (V ≥ 0.87). CFA eliminated 5 weak items, leaving 40 valid items with excellent reliability (alpha = 0.958). Indicator CSI scores reflected